2020
DOI: 10.1093/jbcr/irz196
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Severe Burns to the Breast in Pediatric Patients: A 10-Year Experience

Abstract: The breast and anterior chest are the most commonly burned part of the trunk. Burn injuries to the breast can be associated with pain, asymmetries, and significant social stigma. Burns to the breast bud in the young female may inhibit normal breast development and result in either significant asymmetries or amastia, making the treatment of breast burn injuries challenging. A retrospective chart review was conducted on all female patients under the age of 21 years admitted to our institution for breast burn inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Furthermore, as the breast bud is hidden deep into the subcutaneous tissue, breast mound development may ensue later in puberty even in the absence of the NAC. 1,4,5,10,[13][14][15][16][17] As sheet grafts contract less than meshed grafts and result in better skin texture, they are preferred in the acute care setting. 18,19 When scars are limited to the skin and the breast bud is spared, the pubertal breast parenchyma will develop underneath a contracted skin envelope, leading to deformity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, as the breast bud is hidden deep into the subcutaneous tissue, breast mound development may ensue later in puberty even in the absence of the NAC. 1,4,5,10,[13][14][15][16][17] As sheet grafts contract less than meshed grafts and result in better skin texture, they are preferred in the acute care setting. 18,19 When scars are limited to the skin and the breast bud is spared, the pubertal breast parenchyma will develop underneath a contracted skin envelope, leading to deformity.…”
Section: Discussionmentioning
confidence: 99%
“…While we found that thermal injury occurred before or during puberty in approximately 53% of the cases reported in the literature, Sadeq et al noted that 83% of their 96-patient cohort sustained burn injury in the prepubescent period. 10 Pediatric scald injuries to the chest typically affect the skin only; however, deep scalds and flame injuries may involve the breast bud, which is located beneath the NAC. 4 In such instances, conservative acute treatment of the burned NAC is recommended because of its remarkable ability to regenerate from the epithelium of the lactiferous ducts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomedical procedures may include reconstructive or aesthetic surgery . The benefit of reconstructive surgery is its potential to improve functional outcomes and prevent later complications (Piper et al, 2016;Sadeq et al, 2020), whereas cosmetic and aesthetic surgery may be more strongly dictated by psychosocial motivators. For example, stigmatising experiences may be the main motivator of undergoing aesthetic surgery, and such surgery may contribute to the reduction of experiences of teasing and bullying (Johns et al, 2017;Jones et al, 2020) or improve health-related quality of life (Jones et al, 2020).…”
Section: Biomedical and Psychosocial Supportmentioning
confidence: 99%